1988
DOI: 10.1007/bf01871103
|View full text |Cite
|
Sign up to set email alerts
|

Factors responsible for oscillations of membrane potential recorded with tight-seal-patch electrodes in mouse fibroblasts

Abstract: In giant fibroblastic L cells, penetration of a conventional microelectrode brought about marked decreases in the membrane potential and input resistance measured with a patch electrode under tight-seal whole-cell configuration, and repeated hyperpolarizations were often observed upon penetration. Therefore, the question arose whether such leakage artifact is a causal factor for generation of the membrane potential oscillation even in giant L cells. During whole-cell recordings, however, regular potential osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Varying amounts of purified cDNA plasmid (pBluescript) were added directly to the transcription-translation mixture with no RNA polymerase (lane 1), T3 RNA polymerase (0. and C4 (56). However, recent evidence suggests that C1q can also regulate other functions such as cell-mediated cytotoxicity (57), phagocytosis (58), chemotaxis (59), and interleukin-1 production (60) via a receptor-mediated mechanism. A putative receptor for C1q has been isolated and characterized in several human and murine cells including macrophages, lymphocytes, and fibroblasts (61).…”
Section: Discussionmentioning
confidence: 99%
“…Varying amounts of purified cDNA plasmid (pBluescript) were added directly to the transcription-translation mixture with no RNA polymerase (lane 1), T3 RNA polymerase (0. and C4 (56). However, recent evidence suggests that C1q can also regulate other functions such as cell-mediated cytotoxicity (57), phagocytosis (58), chemotaxis (59), and interleukin-1 production (60) via a receptor-mediated mechanism. A putative receptor for C1q has been isolated and characterized in several human and murine cells including macrophages, lymphocytes, and fibroblasts (61).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to generate recurring hyperpolarizations through Ca2' -activated K ' channels was already described in detaiI in the case of mouse fibroblasts [7,8]. Several other cases have been reported recently showing pulsatile calcium rises with associated membrane conductance changes [9-121. It is important to remember here that not all the tested cells responded to stimulation 121, the proportion of non-responsive cells being about 35%.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of C1q used in this study are similar to those found in various tissue sites during injury and inflammation. Previously, using cultured murine fibroblasts [31], mast cells [11], and eosinophils [12], it has been shown that human C1q can induce chemotaxis across species.…”
Section: Discussionmentioning
confidence: 99%